Conceptualising principal leadership of school renewal - Silcox, Steffan; Cavanagh, Rob; MacNeill, Clinton (AARE, 2004)
This paper reports the findings of an investigation into school renewal and leadership that was conducted in 2003. School renewal is a type of whole-school change that engages and excites the school community to promote, accept and embed the change leading to improved student learning. The paper concentrates on the study of leadership of school renewal with specific reference to some of the key influences in implementing a renewal agenda in schools. It provides an invaluable and reflective insight into renewal and change processes in schools. This paper, based on a mixed methodology research format conducted in Western Australia, shows the critical role the principal plays in bringing about school-renewal. The paper concludes by presenting a conceptual framework of principal leadership and school renewal for consideration. In so doing it both challenges and confirms literature and research in the area of leadership and school change. The research has important implications for all school communities.